Surface integrity of polyethylene liners following trunnionosis of a dual modular neck total hip implant. Issue 6 (November 2018) - Spiegelberg, Ben GI; Lanting, Brent A; Howard, James L; Teeter, Matthew G; Naudie, Douglas DR
Background: There has been a trend in the evolution of total hip arthroplasty towards increased modularity; with this increase in modularity come some potentially harmful consequences. Modularity at the neck shaft junction has been linked to corrosion, adverse reaction to metal debris and pseudotumour formation. Aim: The aim of this retrieval study is to assess whether the surface integrity of the polyethylene (PE) liner is affected by metal wear debris in a single implant design series of THA revised for trunnionosis. Methods: A retrieval analysis of thirty dual-taper modular neck hip prostheses was performed; the mean time from implantation to revision was 2.7 years (1.02–6.2). PE liners were analysed using a scanning electron microscope with an energy dispersive spectrometer to assess for metal particles embedded on the liner surface. Serum metal ion levels and inflammatory markers were also analysed. Results: There were small numbers of metal particles present on the PE liners. The mean number of metal particles per liner was four and the particles varied in size from 0.5 µm to 122 µm mean 16 µm. All patients had elevated metal ion levels: cobalt 6.02 µg/l, chromium 1.22 µg/l, titanium 3.11 µg/l. The cobalt:chromium ratio was 7.55:1. Inflammatory markers were also marginally raised (ESR 17; CRP 10). Conclusion: These results suggest that retention of PE liners may be reasonable when performing isolated revision of the femoral component in cases of failure at the modular neck stem junction, especially when the inner diameter of the liner is already optimised for head size and stability.